Design and experimental evaluation of the novel undulatory propulsors for biomimetic underwater robots. (26th July 2021) - Li, Yaxin; Chen, Lingguo; Wang, Yu; Ren, Cheng
Abstract: Inspired by wide and elongated fins of aquatic species, robotic undulatory propulsors are developed to achieve advanced maneuverability. Through biological observation, undulatory fins are typically comprised of more than 100 fin rays to propagate continuous and diverse propulsive waves for agile locomotion. Due to practical engineering restrictions, most robotic undulatory propulsors are characterized by limit number of long fin rays which intersect flexible fin surfaces as backbones and partition them into multiple membrane-like segments. As spatially discrete surfaces affect waves traveling and thrust efficiency, a novel undulatory propulsor has been proposed in this paper. By taking advantage of an arc-shaped fin surface and its material properties, the newly developed undulatory propulsor is equipped with a series of custom designed fin rays, which are only fastened on the inner edge of fin surface so that the unconstrained part is flexural passively to form a smooth fin profile. To discuss appropriate fin surface configurations for such newly developed propulsor, a series of experiments have been conducted to explore the effects of fin surface material, thickness and morphology on thrust and power consumption. Results reveal the fin surface made of nitrile rubber with 2 mm thickness and aspect ratio of 0.33 is highly recommended when taking into account both propulsive forces and loads suffered by fin rays' actuators. To validate the improvement of thrust efficiency, comparison experiments have been carried out between the conventional and the newly developed undulatory propulsors. The findings indicate smooth sinusoid-like fin profiles contribute to wave propagation, which makes the newly developed undulatory fin outperform the conventional one. Finally, a rajiform-inspired robot prototype has been introduced to assess multi-DOFs maneuverability. The experiments show the biomimetic robot can achieve diverse locomotion including swimming forward, turning in-place and rising/diving propelled by a pair of undulatory propulsors.